Desain UI UX Aplikasi Penjualan dengan Menyelaraskan Kebutuhan Bisnis menggunakan Pendekatan Design Thinking - Angelina, Kristin; Sutomo, Erwin; Nurcahyawati, Vivine (LPPM POLITEKNIK LP3I BANDUNG, 2022)
Alignment between business needs and Information Technology (IT) strategy is one of the main factors for the success of a business. One of them is about the interface design of the application used by the user. The current condition in the company is that marketing and sales activities only use social media such as WhatsApp and Facebook. These cause problems in two business activities, namely a less broad market coverage, frequent barriers to communication, less efficient delivery, and an obstacle to the recording by employees. This research aims to design a sales application user interface that suits business needs using a Design Thinking approach by collecting user characteristics using the User Persona tool. The test uses Usability Testing by giving 4 User Scenarios to each respondent to run and complete on the prototype. The test results show that respondents can complete all User Scenarios in the first iteration by 100%. Based on the test results, the design is good, in line with business needs, and accepted by potential users.